INVENTORY OF TRADITIONAL PROPERTY OF BESEMAH TRIBE IN JOKOH SUB-DISTRICT, DEMPO DISTRICT, PAGAR ALAM CITY - Dimas Dwi Arso; Edytiawarman Edytiawarman; Slamet Muljono (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
This research aims to know and understand the utilization of heritage in indigenous peoples in Besemah tribe, and to know and understand the efforts of indigenous peoples in the tribe of Besemah to preserve their inheritance. In this study the author used an empirical approach by conducting interviews on Jokoh and the head of Adat in the village of Jokoh. As for the material interviewing is about the existence of heirloom in the tribe of Besemah covering anything, then conducted analysis of the legal certainty given to the Adat law community when there is a violation committed of Adat heirloom and how the procedure is done in conducting the management of the estate so that later known the level of awareness of the law of indigenous peoples to its inheritance. The results of the research is the inheritance in indigenous peoples in the tribe of Besemah consisting of the House of Baghi, Tanah, and Keris Serunting Sakti. Then the efforts of indigenous peoples to the people of adat in preserving their inheritance is by doing traditional ceremonies that are attended by community leaders, people's people, and rural residents. As in the house Baghi there is a pillar-set ceremony (Sedekah Negah Ka Tiang), the ceremony of raising a cam (Sedekahnupload Mubungan), ceremony occupies the house (Sedekah Nunggu Ghumah), and the ceremony to test the house (Sedekah Nyimak Ghumah). In addition to the keris, the traditional ceremony is done as a ritual of bathing the Kris as an apology and forgiveness to the almighty for all the mistakes that have been done and ask for all the efforts made in order to Get ease in various things, cheap sustenance, healthy community prosperous, and safe village